The Effectiveness of Problem-Based Learning Utilizing Dienes Blocks on Improving Students’ Divergent Thinking in Elementary School - Tasripin; Musyafa, Helmi Rizki; Hendriana, Heris ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The inability of primary school students to solve mathematical problems using multiple strategies, often rigidly adhering only to methods taught by the teacher, highlights a critical issue: a low level of Divergent Thinking. This study aims to investigate the effectiveness of the Problem-Based Learning (PBL) model utilizing Dienes Blocks in enhancing the Divergent Thinking skills of fourth-grade students in whole number operations. The research employed a quantitative One-Group Pretest-Posttest Design involving a sample of 30 students from a public elementary school in Cimahi City. The intervention was conducted over two meetings, focusing on guiding students through the PBL process to discover and articulate various methods for solving calculation problems. Data were collected using a six-item essay test designed to measure the students' fluency and flexibility in problem-solving strategies, a core indicator of Divergent Thinking. The findings indicate a significant improvement in students' Divergent Thinking ability after the implementation of the PBL model with Dienes Blocks. The increase in scores, analyzed using the N-Gain method, was categorized as moderate. This suggests that the combination of authentic problem contexts provided by PBL and the concrete manipulation offered by Dienes Blocks effectively enables students to break free from rote memorization and explore alternative problem-solving pathways. The study concludes that this integrated approach is an effective strategy for fostering cognitive flexibility and creativity in elementary mathematics education.